Capacitor-clamped LLC resonant converter operating in capacitive region for high-power-density EV charger - Wu, Jiayang (2022)
LLC resonant converter is one of the most commonly adopted topologies for electric vehicle (EV) battery charging. However, due to the wide variation range of battery voltages, applying conventional LLC resonant converters usually results in relatively larger magnetic size and lower power density. This article presents a novel approach to improve the power density performance of LLC resonant converters for EV charging. It leverages the existing capacitor-clamped LLC topology, which was originally proposed for applications needing overcurrent protection, while innovatively operating the converter in the capacitive (rather than inductive) region of conventional LLC resonant converters. Results in this work using our proposed design method show that when working in the capacitive region, the capacitor-clamped LLC converter can not only realize zero-voltage switching in the MOSFETs and zero-current switching in the output diodes but also significantly reduce the flux linkage requirement in the transformer compared to conventional LLC. This leads to an elegant solution that optimally minimizes the size of magnetics for increased power density while reducing costs. The merits of the capacitor-clamped LLC converter with the proposed design method are validated by a 400 W, 200 V input, 125-210 V output range prototype, which achieves an efficiency of 98.13% at the maximum output power.